2012
DOI: 10.1080/1745039x.2012.697351
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary protein and amino acid levels on the expression of selected cationic amino acid transporters and serum amino acid concentration in growing pigs

Abstract: The absorption of lysine is facilitated by leucine, but there is no information regarding the effect of crude protein, lysine and leucine levels on the expression of cationic amino acid transporters in pigs. Therefore, an experiment was conducted with 20 pigs (14.9 +/- 0.62 kg initial body weight) to evaluate the effect of two protein levels, and the content of lysine, threonine, methionine and leucine in low crude protein diets on the expression of b(0,+) and CAT-1 mRNA in jejunum, Longissimus dorsi and Semit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 20 publications
2
25
1
3
Order By: Relevance
“…Variations in CAT1 expression in the skeletal muscle of pigs due to different dietary AA levels have been reported. García-Villalobos et al (2012) found that adequate, as compared to deficient levels of Lys, Thr, and Met, increased the expression of CAT1 in LD. In contrast, we found that excess Leu or excess LIV did not affect CAT1 expression in the LD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variations in CAT1 expression in the skeletal muscle of pigs due to different dietary AA levels have been reported. García-Villalobos et al (2012) found that adequate, as compared to deficient levels of Lys, Thr, and Met, increased the expression of CAT1 in LD. In contrast, we found that excess Leu or excess LIV did not affect CAT1 expression in the LD.…”
Section: Discussionmentioning
confidence: 99%
“…The transporter b 0 , + AT exchanges Lys for neutral AA, particularly Leu Majumder et al, 2009) AT that is coupled with the efflux of Leu (Pineda et al, 2004). We recently observed reduced expression of b 0 , + AT in growing pigs (García-Villalobos et al, 2012;Morales et al, 2013) fed excess Leu diets, and surplus Ile failed to correct the reduction (Cervantes-Ramírez et al, 2013). However, there is limited information regarding the effect of adding surplus Ile and Val to diets with excess Leu on the abundance of transport systems for BCAA and cationic AA (Lys) in growing pigs.…”
Section: Introductionmentioning
confidence: 99%
“…The b 0,+ system, which exchanges Leu for Lys (Torras-Llort et al, 2001), is the most important Lys transporter in the small intestine, and the absorption of Lys by b 0,+ is coupled with Leu efflux (Pineda et al, 2004). However, excess levels of dietary Leu appear to reduce Lys availability by decreasing the expression of b 0,+ (García-Villalobos et al, 2012). Leu stimulates muscle protein synthesis in pigs, and this stimulation is dependent on amino acid availability, but excess Leu may affect Lys absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Morales et al (2012) also found a significant increase in the expression of b 0,+ in jejunum of growing pigs fed low CP, as compared to PB-AA (11.0 vs 19.0%) wheat-based diets. Yue and Qiao (2008) observed that reducing dietary CP concentration from 23.1 to 17.2% decreased the villous height in duodenum and jejunum; this suggests a decrease in the number of small intestine absorptive cells.…”
Section: Discussionmentioning
confidence: 65%
“…The b 0,+ system exchanges Leu for Lys (Torras-Llort et al, 2001), indicating that the intestinal absorption of Lys is coupled with the efflux of Leu. A recent report shows that the dietary content of Leu and Lys affects the absorption of Lys (García-Villalobos et al, 2012). F-AA diets not only contain lower Arg and Leu levels but also a high percentage of free Lys, from 44% (Kerr et al, 2003) to 70% (Barrera et al, 2004) of total Lys.…”
Section: Introductionmentioning
confidence: 99%